(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
The problem of antibiotic resistance in birds necessitates the search for alternatives. This study evaluated the effect of dietary inclusion of turmeric (Curcuma longa) on the intestinal parasite infestation and egg-laying performance of Japanese quails (Coturnix japonica). Forty-five points of lay quails were randomly assigned to three treatments: T1 received 3g of turmeric per 1 liter of water, T2 received 1 tea spoon (4.2g) of dewormer (Bactro-expeller) per 3 liters of water, and T3 served as the control without any test ingredient. The experiment lasted for six weeks, with three replicates of five quails each. Egg quality parameters such as albumen height, egg weight, yolk index, and yolk width were significantly affected by the treatments (P<0.05). Analysis revealed the presence of intestinal parasites, with two cases of Strongyloides spp. in the turmeric-fed group and one case of Ascaridia spp. in the control. However, the dewormer-treated group showed no signs of intestinal parasites. The study concludes that turmeric inclusion in quail diets does not adversely affect egg performance and quality. However, it is ineffective in controlling Strongyloides spp. and should not be relied upon as a preventive or control measure for intestinal parasites. Instead, dewormers should be used, with strict adherence to dosage and withdrawal periods, by comparing turmeric-based diets with conventional worm expellers and evaluating their influence on quail egg production.